Comparative analysis of nucleosides, nucleobases, and amino acids in different parts of Angelicae Sinensis Radix by ultra high performance liquid chromatography coupled to triple quadrupole tandem mass spectrometry. Issue 6 (22nd January 2019) - Qu, Cheng; Yan, Hui; Zhu, Shao‐Qing; Qian, Yi‐Yun; Zhou, Gui‐Sheng; Guo, Sheng; Zhu, Zhen‐Hua; Zhang, Sen; Qian, Da‐Wei; Duan, Jin‐Ao
Abstract: A rapid and sensitive ultra high performance liquid chromatography coupled to triple quadrupole tandem mass spectrometry method was established and employed to determine 21 nucleosides, nucleobases, and amino acids in 60 samples from different parts of Angelicae Sinensis Radix. The established methods were validated by good linearity ( r 2 > 0.9937), limits of detection (0.12–77.75 ng/mL), limits of quantitation (0.31–272.13 ng/mL), intra‐ and interday precisions (RSD ≤ 4.84%, RSD ≤ 6.26%), stability (RSD ≤ 5.92%), repeatability (RSD ≤ 7.14%), recovery (91.4–103.4%), and matrix effects (0.92–1.03). Chemical comparative analysis revealed that the content of total analytes in four parts of Angelicae Sinensis Radix were different, and exhibited the order: Head (14.89 mg/g) > Body (10.15 mg/g) > All (8.22 mg/g) > Tail (6.23 mg/g). Principal component analysis showed that the samples could be classified into four groups in accord with four different parts of Angelicae Sinensis Radix. The results could provide a scientific basis and reference for the quality control of Angelicae Sinensis Radix, and may be conducive to further research on the pharmacological activities of Angelicae Sinensis Radix.